Penampilan Kayu Kelapa (Cocos nucifera Linn) Bagian Dalam yang Dimampatkan Performance of Densified Inner-Part of Coconut Wood (Cocos nucifera Linn) - Isna Yuniar Wardhani; Surjono Surjokusumo; Yusuf Sudo Hadi; Naresworo Nugroho (Jurnal Ilmu dan Teknologi Kayu Tropis, 2006)
The inner-part of coconut wood has low to medium density, which have not been utilized yet optimally as construction material. The purpose of this study was to improve the properties of inner-part of coconut wood by densification, such as it can be considered as a substitute of wood. Pre-treatments were steaming (a1) and boiling (a2) at 120°C for 15 minutes, and pressing temperature were 150°C (b1) and 175°C (b2). Deformation targets were 10% (c1), 20% (c2) and 30% (c3) from the initial thickness. The results indicated that the treatments did not affect to some of the densified wood properties. The appearance of panel surface was smooth and shine, but darker than that of solid. The increasing of density was 4.43 ~ 27.21% with strain recovery of 0.17 ~ 0.52 after soaking in water for 24 hours at room temperature.